"Microscopic evidences of heavy metals distribution and anatomic alterations in breaching‐leaves of Cupressus lindleyi growing around mining wastes". Issue 9 (12th June 2014) - Juan Miguel, Gómez‐Bernal; Ofelia, Morton‐Bermea; Esther Aurora, Ruiz‐Huerta; Maria Aurora, Armienta‐Hernández; Dávila Osiel, González
ABSTRACT In this article a study of the distribution of heavy metals in Cupressus lindleyi breaching‐leaves was done in Taxco, Guerrero. At the same, heavy metals micro‐localization was conducted in the breaching‐leaves to understand the structural changes provoked by mining waste on plants. The most abundant contaminants in soils, tailings and different plant organs (roots, stems, and leaves) were Zn, Mn, and Pb. Nevertheless, As was more accumulated in the stem and breaching‐leaves. The translocation factor and the bio‐concentration factor were less than 1. The structural changes observed were the great accumulation of starch grains and phenolic compounds in the palisade parenchyma, changes in the hypodermis cell wall and necrotic zones in the palisade parenchyma. The distribution of heavy metals in breaching‐leaves tissues was homogeneous in most of the elements. These results showed that C. lindleyi is a species that can be employed in phytostabilization of contaminated zones with mining waste because it is a native plant that does not require a lot of conditions for its development. Microsc. Res. Tech. 77:714–726, 2014. © 2014 Wiley Periodicals, Inc.